Undergraduate psychiatry CBME curriculum revision: The process and the way ahead - Sujata Sethi; Bheemsain Tekkalaki; Nilima Shah; CA Smitha; Rajesh Kumar (Indian Journal of Psychiatry)
Nationa Medical Commission (NMC) had recently undertook the revision of Undergraduate CBME curriculum. the Authors were involved in Psychiatry curriculum revision. In this paper, authors explain the process of revision, the rationale behind the changes made and make specific suggestions for the better implementation of the revised curriculum.